The Development of Interactive Instructional Media Oriented to Creative Problem Solving Model on Function Graphic Subject - Dessy Sugiharni, Gusti Ayu (Journal of Education Reseach and Evaluation, 2018)
The main purpose of this research was to result Interactive Instructional Media Oriented to Creative Problem Solving Model. The method of this research used research and development method by 4-D of development model those were consisted by Define Stage, Design Stage, Develop Stage and Disseminate Stage. However, this research was limited to Develop. The research subjects on individual limited test were as much 2 students, on field trials were as much 20 students. Instrument those were used to get the data in this research were questionnaire and documentation. Technical that was used to analyse the data was percentage descriptive counting. The result of this research showed that development of Interactive Instructional Media Oriented to Creative Problem Solving Model had gone well that was proved by means of learning result was 81.10 when the simulation of using interactive instructional media